PARTISIPASI BADAN PERMUSYAWARATAN DESA (BPD) DALAM IMPLEMENTASI ALOKASI DANA DESA (Studi Kasus di Kecamatan Leksono Kabupaten Wonosobo) - , Sujatmiko, Drs ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Alokasi Dana Desa (ADD) is financial aid as from Pemerintah Kabupaten Wonosobo to pemerintah desa derived from APBD Kabupaten Wonosobo that is intended to finance a program of the pemerintah desa in carrying out the activity of government and community empowerment. This research aiming to know and explains how is the participation the Badan Permusyawaratan Desa (BPD) implementation ADD years 2008 in Kecamatan Leksono, Kabupaten Wonosobo and to know factors what course that can affect participation a member of with implementation the ADD years 2008 in Kecamatan Leksono Kabupaten Wonosobo. The factors influencing participation rules are : the consistency of regulation, the quality of human resources, the structure of the organizations and self reliance. Information collected through an interview and analysis of secondary data. The result showed less / low participation with implementation ADD. Analysis of influential factors which show that the consistency of the regulation does not affect the participation of BPD in the ADD implementation